Judgment of Alignment and Analysis of cognitive learning dimensions of objectives and assessment strategies provided by a selected textbook used in an Environmental Science Course in one high school in Abu Dhabi, UAE - RAHHAL, PATRICK GEORGE (2017)
This present study evaluated the Environmental Education course using a textbook offered in one of Abu Dhabi, UAE schools as a main reference. The textbook was analysed by judging alignment between learning objectives and assessment strategies using Revised Bloom’s Taxonomy as a tool. The research done was qualitative and aimed at classifying the learning outcomes and the different types of assessment into different cognitive learning processes according to the RBT. In addition, knowledge dimension for each item was investigated. The results of the study showed that the textbook was able to provide students with the opportunity to develop their cognitive skills at different levels. This is shown through the assessments provided by the textbook which enabled students to develop their critical thinking and problem-solving skills. In order to have an unprejudiced analysis in the study, objectives and assessments were chosen as only criteria to judge alignment whereas teaching factor was not involved in the study since it can vary tremendously according to situations and learning environments. The study acknowledged the teachers’ role and recommended continuous professional development in Environmental education. In conclusion, the study asserted on the necessity of engaging next generation of students in becoming the problem solvers of the emerging Environmental threats.